2010
DOI: 10.5551/jat.3319
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Intermittent Hypoxia and Metabolic Syndrome; the Effect of being Overweight: the CIRCS Study

Abstract: Aim:We investigated whether nocturnal intermittent hypoxia, a surrogate marker for obstructive sleep apnea, is associated with metabolic syndrome and its components among Japanese. Methods: We examined 1,710 male and 2,896 female community-dwelling Japanese aged 40 to 69, who participated in annual cardiovascular examinations and investigations of sleep. Nocturnal intermittent hypoxia was estimated based on a 3% oxygen desaturation index measured with pulse-oximetry during sleep. No, mild and moderate-to-sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…Previous studies demonstrated the possible association between sleep apena and visceral obesity 8,[17][18][19] 20) , and recent studies reported that obese subjects with sleep apnea also suffer from daytime hypoadiponectinemia 21,22) . Our recent study showed daytime hypoadiponectinemia and nocturnal falls in circulating adiponectin concentrations in patients with severe OSAS, in part due to hypoxic stress 9) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the possible association between sleep apena and visceral obesity 8,[17][18][19] 20) , and recent studies reported that obese subjects with sleep apnea also suffer from daytime hypoadiponectinemia 21,22) . Our recent study showed daytime hypoadiponectinemia and nocturnal falls in circulating adiponectin concentrations in patients with severe OSAS, in part due to hypoxic stress 9) .…”
Section: Discussionmentioning
confidence: 99%
“…The median value of 3% ODI was 5.4 on the first night and 4.8 on the second night (p for difference = 0.95, Wilcoxon's signed-rank test). Spearman's rank correlation coefficient was 0.81 (p<0.001) 25) .…”
Section: Discussionmentioning
confidence: 99%
“…Because apneic episodes do not always induce oxygen desaturation, we were unable to accurately detect the presence of very mild NIH. However, the sensitivity and specificity of pulse oximetry are high 29) , as well as the reproducibility 25) . In addition, the convenience of pulse oximetry for assessing intermittent hypoxia at home and its utility in providing an early diagnosis and treatment for patients with NIH have been documented 7,43) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recommended that patients at risk for hypoxic conditions be monitored using pulse oximetry. 12,14,[33][34][35][36][37] Hypoxia is commonly found in the elderly 38 and those at risk for coronary vascular disease, 39 coronary artery disease, 39 sleep disordered breathing, 39 disorders of balance, hypertension, 39 chronic migraines, and anxiety and mood disorders, 39 all of which can be present within a population of chiropractic patients. See Table 1 for a complete list of clinical signs and symptoms indicating use of pulse oximetry.…”
Section: Conceptual Model Of Pulse Oximetry In a Chiropractic Settingmentioning
confidence: 99%